2011
DOI: 10.1016/j.fcr.2011.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of winter cover crop species and planting methods on maize yield and N availability under irrigated Mediterranean conditions

Abstract: Under semiarid Mediterranean conditions irrigated maize has been associated to diffuse nitrate pollution of surface and groundwater. Cover crops grown during winter combined with reduced N fertilization to maize could reduce N leaching risks while maintaining maize productivity. A field experiment was conducted testing two different cover crop planting methods (direct seeding versus seeding after conventional tillage operations) and five different cover crops species (barley, oilseed rape, winter rape, common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 48 publications
4
46
1
3
Order By: Relevance
“…Similar results were obtained in other studies (Rannels and Wagger 1996, Hanly and Gregg 2004, Gabriel and Quemada 2011 but not in the studies where maize residues (maize was intensively fertilised with N) were chopped and left on the field (Salmerón et al 2011). The amount of N accumulated in nonleguminous cover crops namely depends on the available soil N min , while in the case of symbiotically active legumes, the majority of N accumulated in individual plants mainly occurs due to N fixation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar results were obtained in other studies (Rannels and Wagger 1996, Hanly and Gregg 2004, Gabriel and Quemada 2011 but not in the studies where maize residues (maize was intensively fertilised with N) were chopped and left on the field (Salmerón et al 2011). The amount of N accumulated in nonleguminous cover crops namely depends on the available soil N min , while in the case of symbiotically active legumes, the majority of N accumulated in individual plants mainly occurs due to N fixation.…”
Section: Discussionsupporting
confidence: 79%
“…Kramberger et al 2009, Thorup-Kristensen and Dresbøll 2010, Campiglia et al 2011, Salmerón et al 2011. However, many researchers have studied mixtures of leguminous and non-leguminous winter cover crops in anticipation of the agricultural or ecological advantages of such binary mixtures (e.g.…”
mentioning
confidence: 99%
“…The SPAD meter was used according to methods recommended by Salmerón et al (2011), Víg et al (2012, and Yang et al (2012). At the V12 crop stage, the SPAD meter was used on five randomly selected plants per plot.…”
Section: Cornmentioning
confidence: 99%
“…However, research has found differing annual crop yield responses with RCC. Corn grain and silage yield decreases have been reported with use of RCC (Raimbault et al, 1990;Kessavalou and Walters, 1997;Thelen and Leep, 2002;Singer and Kohler, 2005;McDonald et al, 2008;Kramberger et al, 2009;Salmerón et al, 2011;Krueger et al, 2012;Reese et al, 2014). A 15% corn yield increase was observed in 2 out of 3 yr in a study conducted on sandy soils in Wisconsin with no N application to the RCC and with low RCC biomass production .…”
mentioning
confidence: 95%